Mismatch-strain-driven leaf rolling in monocot leaves - Lim, Gao Zhi (Nanyang Technological University, 2022)
This report explores and studies the leaf rolling or folding effect due to mismatch strain in plant leaves. Leaf samples will be obtained and allowed to dehydrate for various time periods. They will then be processed using standard histology protocols and analyzed. Plant leaves often undergo deformation when their environmental conditions drastically change. When dehydrated, many species of plants are able to curl or fold their leaves up to reduce the exposure to sunlight as well as reduce water loss through transpiration. As the leaves undergo such deformation, the strain of each side of the leaves will be different and the objective of this report is to obtain the correlation between the cellular structure of the leaves and their rolling behavior during dehydration. This report will be useful of future reference when observing the rolling effect of leaves in other plants. Furthermore, recommendations for future work will be discussed for the improvement of similar experiments.